Effects of road clearings on movement patterns of understory rainforest birds in central Amazonia - Laurance, Susan G.W.; Stouffer, Philip C.; Laurance, William F. (Conservation Biology, 2004)
The impacts of potential linear barriers such as roads, highways, and power lines on rainforest fauna are poorly understood. In the central Brazilian Amazon, we compared the frequency of local movements (≤300 m long) of understory birds within intact forest and across a 30- to 40-m-wide road over a 2-year period. Rainforest had regenerated along some road verges, to the extent that a nearly complete canopy was formed in some areas, so we also assessed whether this facilitated bird movement. Movement data were determined from 1212 recaptures of 3681 netted birds at six study sites. The road significantly inhibited total bird movement across roads at five of the six sites. Bird foraging guilds varied in their responses to the road and different ages of regrowth. Movements of frugivorous and edge and gap species were not inhibited at any site, whereas most forest-dependent insectivores (mixed-species flocks, terrestrial species, and army-ant followers) had markedly inhibited road-crossing movements, except at sites with extensive regrowth. Solitary understory species were especially vulnerable, rarely crossing even roads overgrown by tall regrowth. For sensitive species, road-crossing movements were inhibited because individuals tended to avoid both edge-affected habitat near the road and the road clearing itself. Our results suggest that even narrow roads with low traffic volumes can reduce local movements of many insectivorous birds in Amazonia.
Keywords: Avifauna; Clearance Rate; Rainforest; Road Construction; Species Conservations; Understory; Amazonia; South America; Aves; Formicidae